Targeting Nrf2/KEAP1 signaling pathway using bioactive compounds to combat mastitis - Muhammad Zahoor Khan; Liangliang Li; Yandong Zhan; Huang Binjiang; Xiaotong Liu; Xiyan Kou; Adnan Khan; Abdul Qadeer; Qudrat Ullah; Khalid J. Alzahrani; Tongtong Wang; Changfa Wang; et al. (Frontiers in Immunology)
Mastitis is a common inflammation of mammary glands that has a significantly impact on dairy production and animal health, causing considerable economic burdens worldwide. Elevated reactive oxygen species (ROS) followed by oxidative stress, apoptosis, inflammatory changes and suppressed immunity are considered the key biomarkers observed during mastitis. The Nrf2/KEAP1 signaling pathway plays a critical role in regulating antioxidant responses and cellular defense mechanisms. When activated by bioactive compound treatment, Nrf2 translocates to the nucleus and induces the expression of its target genes to exert antioxidant responses. This reduces pathogen-induced oxidative stress and inflammation by inhibiting NF-kB signaling in the mammary glands, one of the prominent pro-inflammatory signaling pathway. Here, we summarize recent studies to highlight the therapeutic potential of Nrf2/KEAP1 pathway in the prevention and treatment of mastitis. Collectively this review article aims to explore the potential of bioactive compounds in mitigating mastitis by targeting the Nrf2/KEAP1 signaling pathway.